Nilai-nilai Moral dan Budaya dari Beberapa Karya Sastra Indonesia dan Kontribusinya dalam Membangkitkan Semangat Nasionalis - Henrikus Joko Yulianto (HISKI, 2009)
The oral literary tradition that has developed in various areas in the Indonesian archipelago is a heritage that gives specific colors to Indonesian literature. The rapid development of science during this global era, especially in electronic media, has given significant influences to the change of social behavior and culture. In the midst of confusions and restlessness in the search for meaning and identities, it may be a good idea to look back and interpret the literary work: from various parts of the archipelago, especially those which were once only delivered orally, such as folktales, legends, ballads or myths These works, like classic works, contain various socio-cultural values that play important roles in actuaiizng the nation's identity and in strengthening the spirit of nationaitsm brotherhood and interaction with the surrounding nature.